Association of non-alcoholic fatty liver disease with left ventricular changes in treatment-naive patients with uncomplicated hypertension - Catena, Cristiana; Brosolo, Gabriele; Da Porto, Andrea; Donnini, Debora; Bulfone, Luca; Vacca, Antonio; Soardo, Giorgio; Sechi, Leonardo A. (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Cardiac structural and functional changes have been demonstrated in patients with non-alcoholic fatty liver disease (NAFLD). Because of the frequent association of NAFLD with hypertension, we aimed to examine the relationship of liver steatosis with left ventricular (LV) changes in patients with hypertension. Materials and methods In a cross-sectional study, we included 360 untreated, essential hypertensive patients who were free of major cardiovascular and renal complications. Liver steatosis was assessed by three different biochemical scores (NAFLD Liver Fat Score, LFS; Fatty Liver Index, FLI; Hepatic Steatosis Index, HSI). Echocardiography was performed with standard B-mode and tissue-Doppler imaging. Results LV hypertrophy was present in 19.4% and LV diastolic dysfunction in 49.2% of patients who had significantly higher body mass index (BMI), blood pressure (BP), and homeostatic model assessment (HOMA) index and higher frequency of the metabolic syndrome and liver steatosis that was defined by presence of 2 or more positive scores. LV mass index increased progressively across patients who had none, 1, or 2 or more liver steatosis scores, with associated progressive worsening of LV diastolic function. LV mass index was significantly and positively correlated with age, BMI, BP, HOMA-index, LFS, and HSI. Logistic regression analysis showed that age, BP, and liver steatosis scores independently predicted LV hypertrophy and diastolic dysfunction. Liver steatosis independently predicted LV dysfunction but not LV hypertrophy even after inclusion in analysis of the HOMA-index. Conclusion NAFLD is associated with LV hypertrophy and diastolic dysfunction in untreated patients with hypertension. In hypertension, NAFLD could contribute to LV diastolic dysfunction with mechanisms unrelated to insulin resistance.